Content validity and psychometric evaluation of Functional Assessment of Chronic Illness Therapy-Fatigue in patients with psoriatic arthritis - David Cella; Hilary Wilson; Huda Shalhoub; Dennis A. Revicki; Joseph C. Cappelleri; Andrew G. Bushmakin; Elizabeth Kudlacz; Ming-Ann Hsu (SpringerOpen, 2019)
Abstract Background To evaluate the measurement properties (e.g., content validity, reliability, and ability to detect change) of the Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue scale in patients with active psoriatic arthritis (PsA). Methods One-on-one semi-structured qualitative interviews with adult patients with active PsA evaluated the content validity of FACIT-Fatigue. Quantitative measurement properties were evaluated using data from phase III tofacitinib randomized controlled trials (RCTs) in PsA: OPAL Broaden (NCT01877668) and OPAL Beyond (NCT01882439). Results Of 12 patients included in the qualitative study, 2 (17%) had mild, 8 (67%) had moderate, and 2 (17%) had severe PsA disease activity; 7 (58%) attributed fatigue to PsA, and 7 (58%) rated fatigue as important or extremely important. Most patients considered the FACIT-Fatigue items relevant to their PsA experience, and understood item content and response options as intended. In the psychometric analysis of RCT data, a second-order confirmatory factor model fit the data well (Bentler's Comparative Fit Index ≥0.92). FACIT-Fatigue demonstrated good internal consistency (Cronbach's coefficient α ≥ 0.90), test-retest reliability (Intraclass Correlation Coefficient ≥ 0.80) and a strong correlation with SF-36 Vitality (r > 0.80). A robust relationship between disease activity (based on Patient's Global Assessment of Psoriasis and Arthritis) and FACIT-Fatigue was observed (effect sizes > 1.4), with clinically important difference for the FACIT-Fatigue total score estimated as 3.1 points, and the responder definition estimated as a 4-point improvement for FACIT-Fatigue total score. Conclusion Fatigue was confirmed to be an important symptom to patients with PsA, and FACIT-Fatigue was found to be a reliable and valid measure in this population.